Supervivencia organizativa y legitimidad social : el caso de la Biblioteca Pública Piloto de Medellín (1952-2002) - Espinal Monsalve, Nora Elena; Gutiérrez Hidalgo, Fernando (El Colegio de México, 2014)
The purpose of this research is showing how organizations with high legitimacy in their environment survive to economic difficulties, are able to modify negative pressures exerted on them, and become an example for others. For that, we have studied the case of the Public Pilot Library of Medellin for Latin America. For this study we have done interviews to key people of the library, and we have studied primary and secondary sources related to it. UNESCO founded this library in 1952 and was the second of three major projects to contribute to the cultural progress in the Third World. During the study period (1952-2002) the Library suffered two economic crises which surpassed due to its high social legitimacy. For this analysis we have used the institutional perspective.